(3QSGdI aj YdGeGJ GdehJs - (3GHbQGW GdMcjes ((3eMeO gGTe Hf eMeO Ydi GdcGTGfi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPg cdeGJ efShHI Edi ajdSha ai YdGeGJ GdehJ s
(3BNQgG (B:s
(3aGYde Cf UGMHg jehJ Edi KdGKI CTgQ ef Chd eQV hYdGeI Pdc Cfg jYQV Hg TghI GdHWjN hZQR GdHhd JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3SHgdGQ (B(1517) s
Keywords: (3GdWHs